[Adult] Third Culture Kids: Why Do Early Life International Experiences Matter? - Caselius, Mireka; Suutari, Vesa (Palgrave Macmillan, 2023)
An increasing number of studies have been conducted on children with early life international mobility, that is, on third culture kids (TCKs). In this chapter, we review how TCKs appear in the existing research through the TCKs’ migration journey. We include TCK research that is reported within different disciplines to form a wide perspective on the experiences of this population. We cover different stages of the mobility from pre-departure preparation to cross-cultural adjustment, and further on to the repatriation stage. Finally, we discuss the longer-term challenges and benefits of being an adult third culture kid (ATCK). The review indicates that the time spent abroad has a significant impact on the ATCK’s worldview, education decisions, identity, and future career. It thus highlights the importance of supporting TCKs in the different stages of mobility, despite such practices often still seeming to be overlooked. As an outcome of the review, a future research agenda is suggested to help improve our understanding of TCKs’ international experiences, and the long-term impacts they have on the later life and career of ATCKs. As an implication, it is raised that TCKs offer an attractive pool of employees for companies looking for staff with international competencies.
Keywords: Expatriation; Migration; Expatriate family; Third culture kid; Adult third culture kid; fi=Henkilöstöjohtaminen|en=Human Resource Management|